“What do I know?”: scholastic fallacies and pragmatic religiosity in mental health-seeking behaviour in India - Quack, Johannes (Mental health, religion & culture, 2013)
This paper draws on ethnographic fieldwork on psychiatrists and their patients (their care-givers and their communities) in North India. It addresses the questions as to when and why people approach psychiatrists and religious healers by arguing that approaches assessing “explanatory models” and other knowledge structures relevant to the people's health-seeking behaviour should place more emphasis on the people's strong desire to get well, in any way possible. Secondly, the difference between beliefs rooted in the patients’ life-worlds and explanations suggested to them by experts has to be acknowledged. These insights motivate a shift away from the concept “religion” towards the differentiation between pragmatic and scholastic religiosities. This argument relates back to the Greek meaning of “pragma” understood by Hans-Georg Gadamer as “that within which we are entangled in the praxis of living”.
Published online: 23 May 2012
Gesehen am 11.01.2022